Third head of gastrocnemius - a case report - R Shalini; K V P. Suriyakumari (Wolters Kluwer Medknow Publications, 2013)
Gastrocnemius is a superficial muscle of the posterior compartment of leg. It usually arises by two heads- a medial and a lateral head. A third head of Gastrocnemius has been reported to occur in 2.9 - 5.5% of subjects. This anomaly has been implicated as a cause for popliteal vessel entrapment syndrome.Variations of the heads of origin of Gastrocnemius muscle were studied in 20 lower extremities of ten adult cadavers during routine Popliteal Fossa dissection at Sri Manakula Vinayagar Medical College and Hospital, Puducherry. An accessory third head of Gastrocnemius was found in four lower limbs (20%). This third head originated along with the lateral head of Gastrocnemius.